Molecular structure and vibrational and chemical shift assignments of 3-(2-Hydroxyphenyl)-4-phenyl-1H-1,2,4-triazole-5-(4H)-thione by DFT and ab initio HF calculations - Avci, Davut; Atalay, Yusuf; Sekerci, Mehmet; Dincer, Muharrem (Pergamon-Elsevier Science Ltd, 2009)
The molecular geometry, vibrational frequencies, gauge including atomic orbital (GIAO) H-1 and C-13 chemical shift values and several thermodynamic parameters of 3-(2-Hydroxyphenyl)-4-phenyl-1H-1,2,4-triazole-5-(4H)-thione in the ground state have been calculated by using the Hartree-Fock (HF) and density functional methods (BLYP and B3LYP) with 6-31G(d) basis set. The results of the optimized molecular structure are presented and compared with the experimental X-ray diffraction. The molecule contains one O-H center dot center dot center dot N and one C-H center dot center dot center dot pi (phenyl) intramolecular interactions. The computed vibrational frequencies are used to determine the types of molecular motions associated with each of the experimental bands observed. Data of the title compound display significant structure-correlation and provide the basis for future design of efficient materials having the derivatives of 1,2,4-triazole. Also, calculated I H chemical shift values compared with the experimental ones. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: 3-(2-Hydroxyphenyl)-4-phenyl-1H-1,2,4-triazole-5-(4H)-thione; DFT; HF; GIAO; H-1; C-13 NMR; IR spectra; Structure elucidation; Vibrational assignment